1991
DOI: 10.1152/jappl.1991.70.3.1137
|View full text |Cite
|
Sign up to set email alerts
|

Retention and clearance of 0.9-micron particles inhaled by hamsters during rest or exercise

Abstract: We assessed the retention and clearance of inhaled particles in six anatomic compartments of the respiratory tract. Hamsters were exposed for 45 min to 0.9-micron fluorescent latex particles either at rest (n = 9) or while running on a laddermill (n = 9). Oxygen consumption, which was used to estimate minute ventilation, was continuously monitored. Three animals from each group, rest and exercise, were killed at 10 min, 24 h, or 7 days after the exposure. Morphometric techniques were used to determine the numb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
20
0

Year Published

1996
1996
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(24 citation statements)
references
References 0 publications
4
20
0
Order By: Relevance
“…Our histomorphometric study focused on the small branches of pulmonary arteries adjacent to the bronchoalveolar junction of rats exposed to CAPs. Substantial concentrations of bioavailable compounds may be released from deposited ambient particles in this tissue region because this is the site of highest deposition (25)(26)(27)(28).…”
mentioning
confidence: 99%
“…Our histomorphometric study focused on the small branches of pulmonary arteries adjacent to the bronchoalveolar junction of rats exposed to CAPs. Substantial concentrations of bioavailable compounds may be released from deposited ambient particles in this tissue region because this is the site of highest deposition (25)(26)(27)(28).…”
mentioning
confidence: 99%
“…Zeltner et al (58) administered a dilute aerosol of 0.9-m FMS to guinea pigs, and they documented with histology that the microsphere deposition was almost exclusively alveolar. This suggested that an FMS aerosol in that size range might be used to produce maps of regional ventilation, provided an adequate fluorescence signal could be obtained from postmortem cut lung pieces.…”
Section: Microsphere Aerosols To Map Regional Ventilationmentioning
confidence: 99%
“…Recent observations by Zeltner (unpublished findings) confirm that particle density is highest at the first alveolar duct in the hamster, but deposition is not confined to the first bifurcation; particles also deposit on other bifurcations and on alveolar surfaces. Twenty four hours after exposure, density is equivalent on duct and alveolar surfaces (Zeltner et al, 1988a). Thus, alveolar ducts may indeed receive the largest dose initially, but particles are redistributed and dose equilibrates throughout the deep lung soon after exposure.…”
Section: Species Variation In Depositionmentioning
confidence: 99%
“…A complication is that animals may sleep or be irritated by the aerosol, and thus their activity level will vary as a function of the agent and the exposure. For hamsters at rest or exercising, a linear relationship has been demonstrated between oxygen consumption, a measure of activity, and the total respiratory tract deposition of 0.38-;im (Harbison and Brain, 1983) or 0.9-¿tm particles (Zeltner et al, 1988b) . However, the site of the increased deposition in the respiratory tract varies with particle KEY WORDS: aerosol exposure, regional deposition, species differences, breathing pattern, exposure systems, lung disease.…”
Section: What Type Of Exposure System To Use?mentioning
confidence: 99%